Surviving crises – through education? - Barberis Eduardo; Parreira do Amaral Marcelo (Dipartimento di Culture, Politica e Società - Università di Torino, 2025)
Introducing the themed issue on Surviving crises through education, this article puts education and youth policy in the EU in focus, as European countries have to face challenges in at least three domains: youth incorporation into the labour market; the political participation of young generations; the management of internationally mobile youth. The collection of articles in this issue shows that coordinated and effective outcomes are yet to come.